Typology of Land Conflicts in Special Region of Yogyakarta - Luthfi , Ahmad Nashih (BHUMI: Jurnal Agraria dan Pertanahan, 2023)
Abstract: This paper identifies various structural land conflicts in the Special Region of Yogyakarta in the last 20 years. Using a literature review method, the various conflicts that occurred can be categorized into several typologies, (1) the issue of the transfer of land status from private and communal (village land) to sultanate/pakualaman land; (2) land acquisition for national strategic projects that displace people's managed areas; (3) investment and development in urban areas that displace or reduce the quality of life of the community; (4) various transfers of land use in coastal areas by local governments and the private sector through extractive industry investment, tourism or conservation; (5) ethnic politicization in discriminative land policies. The reading of the various typologies of conflict is produced from three different perspectives, namely the 'agrarian citizenship' approach, 'human rights', and 'politics of access’. These three perspectives also serve as a proposed roadmap to get out of the conflict. Keywords: Land conflict, Roadmap of conflict resolution, Special region of Yogyakarta, Typology